Analysis of the Effectiveness of Online Lectures Against Student Achievements Using the C4.5 Method (Case Study: Faculty of Communication and Information Technology National University): Analysis of the Effectiveness of Online Lectures Against Student Achievements Using the C4.5 Method (Case Study: Faculty of Communication and Information Technology National University) - Vivimaryati Vivimaryati; Agung Triayudi; Ira Diana Sholihati (Institute of Computer Science (IOCS), 2020)
This research is aimed at studying the effectiveness of online lectures on student achievement at the Faculty of Technology and Communication and Information at the National University using the C4.5 Algorithm method. The factors that must be considered in measuring the level of effectiveness of online lectures, namely from the income of parents, attendance and GPA (Grade Point Average) to every student. In the third factor has not been measured with certainty so that the Faculty of Communication and Information and Technology found it difficult to determine what can be changed and improved in quality, which will use the C4.5 method, in the case the author tries to measure these three factors so that eventually a Decision Tree. After doing calculations using the application it will know the level of short comings. Educational quality is something that needs to be considered because it is very influential in the process of student learning, therefore it needs an effort to improve effectiveness in online lectures.